2020
DOI: 10.3201/eid2607.200407
|View full text |Cite
|
Sign up to set email alerts
|

Public Mental Health Crisis during COVID-19 Pandemic, China

Abstract: Rapid identification of mycobacteria to the species level by polymerase chain reaction and restriction enzyme analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
474
2
37

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 584 publications
(525 citation statements)
references
References 7 publications
12
474
2
37
Order By: Relevance
“…Solche Angebote sind niedrigschwellig und kommen ohne den Einsatz personeller Ressourcen aus, was eine breite Nutzung ermöglicht. Public-Health-Ansätze im Sinne eines psychologischen Krisenmanagements für die Allgemeinbevölkerung existierten bisher kaum und entstehen aktuell quasi ad hoc, wie zunächst in China, wo der Fokus auf Telemedizin gelegt wird [45]. Erste Fallstudien aus Deutschland bestätigen erhöhte psychische Belastungen infolge von COVID-19 und unterstreichen den Bedarf für eine Public-Health-Agenda, die Maßnahmen zum Schutz der psychosozialen Gesundheit während der Massenquarantäne hierzulande forciert [46].…”
Section: Diskussionunclassified
“…Solche Angebote sind niedrigschwellig und kommen ohne den Einsatz personeller Ressourcen aus, was eine breite Nutzung ermöglicht. Public-Health-Ansätze im Sinne eines psychologischen Krisenmanagements für die Allgemeinbevölkerung existierten bisher kaum und entstehen aktuell quasi ad hoc, wie zunächst in China, wo der Fokus auf Telemedizin gelegt wird [45]. Erste Fallstudien aus Deutschland bestätigen erhöhte psychische Belastungen infolge von COVID-19 und unterstreichen den Bedarf für eine Public-Health-Agenda, die Maßnahmen zum Schutz der psychosozialen Gesundheit während der Massenquarantäne hierzulande forciert [46].…”
Section: Diskussionunclassified
“…The mental health impact of COVID-19 is significant (Torales et al 2020) and we have seen from previous epidemics of this nature that there can be long-term psychiatric sequelae (Mak et al 2009). This current pandemic has seen an increase in fear and fear-induced behaviours in the general public (Dong & Bouey, 2020) with examples of panic buying in Ireland (Bray, 2020) emphasising the current stress levels of the Irish population. There have been calls for increased mental health care during the COVID-19 pandemic (Xiang et al 2020) and this should include patients attending addiction psychiatry services (Murray, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this study is the rst worldwide assessment of the mental health effects of COVID-19. Previous studies on the psychological impact of COVID-19 have been mostly from China 13,[19][20][21][22][23][24][25]39 The largest of these studies (n = 52,730) that surveyed voluntary public participants, reported symptoms of psychological distress in almost one-third of the participants according to the peritraumatic distress index. 40 Another notable study, on health professionals (n = 1,255), revealed depression, anxiety, and symptoms of general distress in almost half of participants, and sleep disturbances in almost 8%.…”
Section: Discussionmentioning
confidence: 99%